(untitled) (Revista Latino-Americana de Enfermagem, 2010)
The aim of this study was to understand and analyze the potential of a game as a sensitization strategy for the performance of focal groups with adolescents in investigations into values. Twenty nine groups were realized in 10 social institutions of the municipality of Santo André. The sample was composed of 209 adolescents of 15 to 19 years of age. The results indicated that the majority expressed themselves without difficulties, discussing each of the valorative expressions drawn during the game with resourcefulness, involvement and respect for differing opinions, as well as being a method to promote reflection and stimulate debate about social values. Conclusions: The game was adequate for the collection of data. The ludic character allowed the participation of adolescents in an intense, relaxed, enjoyable and interactive way, which facilitated the deepening of discussions on the topic. The evaluation also identified a strong motivation for adolescents to discuss social values.